miR-27a Downregulation Promotes Cutaneous Squamous Cell Carcinoma Progression via Targeting EGFR - Wang, Yinghui; Deng, Xuyi; Dai, Yu; Niu, Xinli; Zhou, Meijuan (Frontiers in Oncology, 2020)
Cutaneous squamous cell carcinoma (cSCC) is the second common malignant cancer around the worldwide and is etiologically linked to ultraviolet radiation. MiRNAs play an important role in the initiation and progression of cancers. However, the functions of miRNAs in cSCC remain to be elucidated. Here, we screened and identified miR-27a as a consistently downregulated miRNA after UVB irradiation in HaCaT cells. It was found that miR-27a expression was significantly decreased in cSCC cells and tissues. In vitro and in vivo experiments showed that miR-27a inhibited cell proliferation and invasion of cSCC cells. Mechanistically, EGFR was identified to be directly targeted by miR-27a and miR-27a suppressed the phosphorylation of EGFR and its downstream NF-κB signaling pathway. Overall, these findings suggest that downregulation of miR-27a promotes tumor growth and metastasis via targeting EGFR and its downstream NF-κB signaling pathway, reminding that miR-27a plays a vital role in the progression of cSCC and could be a new therapeutic target.